2019
DOI: 10.1007/s00167-019-05838-z
|View full text |Cite
|
Sign up to set email alerts
|

Timing of anterior cruciate ligament reconstruction and preoperative pain are important predictors for postoperative kinesiophobia

Abstract: Purpose Fear of movement (kinesiophobia) is a major limiting factor in the return to pre-injury sport level after anterior cruciate ligament reconstruction (ACLR). The aim of this study was to gain insight into the prevalence of kinesiophobia pre-ACLR, 3 months post-ACLR and 12 months post-ACLR. Furthermore, the preoperative predictability of kinesiophobia at 3 months post-ACLR was addressed. Methods A retrospective study with data, which were prospectively collected as part of standard care, was conducted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 65 publications
1
43
1
Order By: Relevance
“…Kinesiophobia prevalence data varies according to what population group is being assessed. For example, it is found in 62% of patients after the reconstruction of the anterior cruciate ligament in the knee, 66.6% of patients with lupus erythematosus, and 75.1% of patients with fibromyalgia [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kinesiophobia prevalence data varies according to what population group is being assessed. For example, it is found in 62% of patients after the reconstruction of the anterior cruciate ligament in the knee, 66.6% of patients with lupus erythematosus, and 75.1% of patients with fibromyalgia [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported by Zhang et al [ 3 ] in 2017 from eight studies comparing incision-to-suture versus a full-time tourniquet regime. Likewise, in 2019, Liu et al [ 84 ] analysed operating times across several tourniquet protocols, evidencing significantly longer surgeries in the absence group compared to the full-time tourniquet group ( P = 0.005). On the other hand, Wang et al [ 12 ] found no difference in surgical duration between shorter tourniquet use during cementation only and longer tourniquet use across 338 procedures; however, their findings were compromised by a high level of heterogeneity across the data.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Wang et al [ 12 ] performed a meta-analysis comparing cementation only versus longer tourniquet use, and found significantly less intraoperative blood loss with long-term tourniquet use. Intraoperative blood loss was also analysed by Liu et al, in 2019, [ 84 ], who found that full-time tourniquet use was correlated with lower intraoperative blood loss compared to absence (1011 samples, P < 0.0001) and cementation only groups (323 samples, P < 0.0001). Previous meta-analyses have reported similar findings [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations